2004
DOI: 10.1177/10883576040190040601
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Autism Spectrum Disorders Among Connecticut School Speech—Language Pathologists

Abstract: This study utilized a rating scale and random sampling of Connecticut school speech—language pathologists about their preprofessional education and current knoWledge of autism spectrum disorders (ASD). The participants had a minimal amount of preprofessional academic or clinical preparation in ASD, and no differences Were found in hoW speech—language pathologists Were trained over the past 30 years. School speech—language pathologists reported relatively stronger knoWledge of the general behavioral and communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 11 publications
3
34
0
Order By: Relevance
“…For example, Stone and Rosenbaum (1988) found that teachers held incorrect beliefs about students with Autism, particularly in the area of cognition, when compared to Autism specialists. Other studies have shown that speech-language pathologists demonstrated inadequate knowledge of strategies for inclusion (Cascella & Colella, 2004). Furthermore, despite demonstration of accurate knowledge about Autism, medical professionals have been shown to make recommendations inconsistent with their knowledge (Kennedy, Regehr, Rosenfield, Roberts & Lingard, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Stone and Rosenbaum (1988) found that teachers held incorrect beliefs about students with Autism, particularly in the area of cognition, when compared to Autism specialists. Other studies have shown that speech-language pathologists demonstrated inadequate knowledge of strategies for inclusion (Cascella & Colella, 2004). Furthermore, despite demonstration of accurate knowledge about Autism, medical professionals have been shown to make recommendations inconsistent with their knowledge (Kennedy, Regehr, Rosenfield, Roberts & Lingard, 2004).…”
mentioning
confidence: 99%
“…Cascella & Colella (2004) investigated the knowledge of Autism spectrum disorders among speech language pathologists. Eighty-two speech-language pathologists working in schools in Connecticut were surveyed.…”
mentioning
confidence: 99%
“…Of school-based SLPs, 90% reported working with children with ASD as part of their caseload [2]. These professionals have received a wide variety of education and preparation to serve this population [3]. One negative consequence of the widely varying educational backgrounds of school-based SLPs is the use of treatment programs that have little supporting evidence of their effectiveness with children with ASD in school settings [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is well understood that children with ASD present specific challenges in assessment and intervention *Address correspondence to this author at the College of Human Ecology, Kansas State University, 238 Campus Creek Complex, Manhattan, KS 66506-1401, USA; Tel: +1 785 532 0802; Fax: +1 785 532 6523; E-mails: deburnet@k-state.edu when compared to other children with receptive, expressive, or pragmatic language disorders [3]. In 2006, the American Speech-Language-Hearing Association (ASHA) issued guidelines for the knowledge and skills needed to work with individuals with ASD [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation